2009
DOI: 10.1111/j.1365-2745.2008.01472.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of cryptogam composition and diversity in Sphagnum‐dominated peatlands: the importance of temporal, spatial and functional scales

Abstract: Summary 1.Changing temperature regimes and precipitation patterns in the Subarctic will impact on vegetation composition and diversity including those of bryophyte and lichen communities, which are major drivers of high-latitude carbon and nutrient cycling and hydrology. 2. We investigated the relative importance of such impacts at different temporal, spatial and plant functional scales in subarctic Sphagnum fuscum -dominated peatlands, comprising both an in situ warming experiment and natural climatic and top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 68 publications
3
57
0
3
Order By: Relevance
“…This result is consistent with the absence of a significant interaction between treatment and DOY for SGR (Table 3). In both treated and untreated plots, Sphagnum growth was stimulated by elevated soil temperatures and dry conditions, a result that has been documented previously (Skre and Oechel 1981;Sonesson et al 2002;Dorrepaal et al 2004Dorrepaal et al , 2006Gunnarsson 2005;Breeuwer et al 2008;Lang et al 2009). However, we did not see a significant difference in soil moisture between treatments.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…This result is consistent with the absence of a significant interaction between treatment and DOY for SGR (Table 3). In both treated and untreated plots, Sphagnum growth was stimulated by elevated soil temperatures and dry conditions, a result that has been documented previously (Skre and Oechel 1981;Sonesson et al 2002;Dorrepaal et al 2004Dorrepaal et al , 2006Gunnarsson 2005;Breeuwer et al 2008;Lang et al 2009). However, we did not see a significant difference in soil moisture between treatments.…”
Section: Discussionsupporting
confidence: 77%
“…Whereas most existing studies have examined the relationships between growth and climate on an annual time scale and/or have substituted space for time by comparing different sites (i.e., Backeus 1988;Callaghan et al 1997;Gunnarsson 2005;Lang et al 2009), we conducted, to our knowledge, the first multi-year analysis on a seasonal time scale at the same site. Lang et al (2009) demonstrated that spatial and temporal scales strongly determined which environmental drivers correlated most with vegetation composition and diversity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…La relative rareté de l'espè-ce sur sphaignes dynamiques, localement en Sologne ou dans l'ensemble de l'aire nationale de l'espèce, trouve vraisemblablement son origine dans les effets allélopathiques exercés par les sphaignes (Duckett & Clymo, 1988) ainsi que dans des effets de compéti-tion pour les ressources. De façon paradoxale, les tourbières où les sphaignes présentent une croissance soutenue sont plus pauvres en microhépatiques que celles où celles-ci sont moins dynamiques (Lang et al, 2009). Les perturbations modérées favorisent donc les microhépatiques au détriment des sphaignes, qui, dans certaines situations, ne laissent pratiquement aucun espace pour la colonisation d'autres bryophytes.…”
Section: A éCologie De Cephalozia Macrostachya Et Valeur Indicatriceunclassified
“…Due to wetness levels and the often meager vascular plant cover, peatlands bring favorable conditions to bryophytes and contribute to a large extent to the diversity of moss and liverwort species, particularly in regions where peatlands are abundant (Minayeva, 2008). Also, in the Northern Hemisphere, the role of peatlands in the upkeep of lichenic diversity is very important (Lang & al., 2009). Nevertheless, Minayeva (2008) reported that the species number of lichens present is quite low compared to the non-peatland lichen flora for any given region.…”
Section: Introductionmentioning
confidence: 99%